Aortic stiffness is independently associated with interstitial myocardial fibrosis by native T1 and accelerated in the presence of chronic kidney disease. (September 2019) - Chen, Mengzhen; Arcari, Luca; Engel, Juergen; Freiwald, Tilo; Platschek, Steffen; Zhou, Hui; Zainal, Hafisyatul; Buettner, Stefan; Zeiher, Andreas M.; Geiger, Helmut; Hauser, Ingeborg; Nagel, Eike; et al.
Abstract: Background: Patients with chronic kidney disease (CKD) have considerable cardiovascular morbidity and mortality. Aortic stiffness is an independent predictor of cardiovascular risk and related to left ventricular remodeling and heart failure. Myocardial fibrosis is the pathophysiological hallmark of the failing heart. Methods and results: An observational study of consecutive CKD patients ( n  = 276) undergoing comprehensive clinical cardiovascular magnetic resonance imaging. The relationship between aortic stiffness, myocardial fibrosis, left ventricular remodeling and the severity of chronic kidney disease was examined. Compared to age-gender matched controls with no known kidney disease ( n  = 242), CKD patients had considerably higher myocardial native T1 and central aortic PWV ( p  ≪ 0.001), as well as abnormal diastolic relaxation by E/e′ (mean) by echocardiography ( p  ≪ 0.01). A third of all patients had LGE, with similar proportions for the presence and the (ischaemic and non-ischaemic) pattern between the groups. PWV was strongly associated with and age, NT-proBNP and native T1 in both groups, but not with LGE presence or type; the associations were amplified in severe CKD stages. In multivariate analyses, PWV was independently associated with native T1 in both groups ( p  ≪ 0.01) with near two-fold increase in adjusted R 2 in the presence of CKD (native T1 (10 ms) R 2, B(95%CI) CKD vs. non-CKD 0.28, 0.2(0.15–0.25) vs. 0.18, 0.1(0.06–0.15), p  ≪ 0.01). Conclusions: Aortic stiffness and interstitial myocardial fibrosis are interrelated; this association is accelerated in the presence of CKD, but independent of LGE. Our findings reiterate the significant contribution of CKD-related factors to the pathophysiology of cardiovascular remodeling.